The designs and applications of a scanning interface with electrical signal detection on the scalp for the severely disabled. Issue 2 (November 2015) - Lin, Chern-Sheng; Lin, Jung-Chih; Huang, Yen-Chen; Lai, Yu-Chen; Chang, Hsing-Cheng
Highlights A scanning interface with electrical signal detection of the head is designed. A algorithm filters noise and reduces misrecognition of the system. The traditional scanning keyboard is modified. The typing time could be reduced. It can obtain more reliable results as 95% success rate.